Analisis terhadap Sistem Kerja Outsourcing Perspektif Manajemen Sumber Daya Manusia Islami - Nurul Rachmah; Wijiharta Wijiharta (At-Tauzi : Jurnal Ekonomi Islam, 2013)
This study aims to determine the pattern of outsourcing work contract systems and to find out how the work contract system practices according to the perspective of Islamic human resource management. This research was conducted at the principal company, with research subjects outsourcing employees. This qualitative research uses data collection techniques through triangulation methods and data analysis techniques using content analysis. The conclusion from the research results are that there are conformity and discrepancy in the practice of outsourcing work systems by vendor companies in terms of Islamic resource management concepts; the appropriate thing is in the event that the perpetrator of the work contract is tamyiz, the contract of agreement is in the form of a work agreement, the form of work as an employee in the production division that produces halal goods, the value (amount) of wages, and the contract period; While things that are not appropriate are the unclear status of the employer (musta'jir) to the employee (ajiir) (employees make work contracts to vendors but work and get wages from the principal company), the unclear working period (principal companies can at any time) time returns to the vendor company), and wages received do not reflect benefits.